Early multicentre experience of ultra-mini percutaneous nephrolithotomy in the UK. (March 2017) - Pullar, Ben; Havranek, Eric; Blacker, Tony J R; Datta, Sam N; Somani, Bhaskar; Sriprasad, Seshadri; Ratan, Hari; Scriven, Sharon; Choong, Simon; Smith, R Daron; Mackie, Simon; Watson, Graham; et al.
Objectives: Ultra-mini percutaneous nephrolithotomy (UMP) is a novel technique recently introduced allowing percutaneous renal access to stones using a specially modified 11 or 13 Fr sheath, a 6 Fr nephroscope, and permits laser fragmentation and stone evacuation. This study aimed to review the early practice of UMP in the UK. Methods: All centres in the UK which had performed UMP were contacted to submit data. Data were submitted to a central database from nine centres around the UK who performed UMP between July 2013 and December 2014. Data were collected on patient, stone, operative factors and outcomes. Results: A total of 32 UMP cases were performed in the contributing centres. Stone size ranged from 7 mm×5 mm to 24 mm×24 mm across the 32 cases, with a mean of 13 mm×10 mm. Stone-free rates were excellent with 31/32 cases stone-free post procedure; 26/32 patients were left without a nephrostomy tube. Complications were uncommon; there were two Clavien 1 complications in this series (6%). Conclusion: This study has shown the efficacy of UMP during its introduction into UK practice. It is likely that UMP will become a useful addition to the armamentarium to treat renal stones, especially smaller stones in the lower pole calyx, and in specialised cases such as paediatric stone disease and in patients with stones in calyceal diverticulae.